Synthesis, Characterization, Molecular Docking and Antimicrobial Activity of Novel Spiropyrrolidine Derivatives. (14th September 2022) - Asad, Mohammad; Arshad, Muhammad Nadeem; Asiri, Abdullah M.; Khan, Salman A.; Rehan, Mohd; Oves, Mohammad
Abstract: The 1, 3-dipolar cycloaddition reaction of the chalcones with azomethine ylide (generated by isatin and sarcosine) has been constructed to functionalize novel spiropyrrolidines. The synthesized compounds (4a–d ) structures were characterized by modern spectroscopic techniques and further corroborated a compound 4a by single crystal X-ray study. The in vitro antibacterial activity of novel spiropyrrolidines was evaluated against the Gram-positive and Gram-negative bacterial strains Bacillus subtillis, Enterococcus faecalis and Escherichia coli, Pseudomonas aeruginosa, respectively. Among them, compound 4c was found the most potent antibacterial agent. The minimum inhibitory concentration (MIC) observed was 75 and 125 µg/mL against all targeted Gram-positive and negative strains respectively. Furthermore, the compounds were also explored for their inhibitory potential against a known therapeutic target and an essential bacterial enzyme, DNA gyrase using computational methods.